1992
DOI: 10.1079/bjn19920108
|View full text |Cite
|
Sign up to set email alerts
|

Influence of low dietary lipid content on anorexia and [14C]glucose uptake in the intestine of zinc-deficient mice

Abstract: Zinc deficiency was induced in adult male mice by feeding them for 8 weeks on a purified semi-synthetic Zn-deficient diet (ZD) containing 90 g lipid/kg (60 g maize oil plus 30 g cod-liver oil). One group was then fed on a low-lipid Zn-deficient diet (ZDLR) containing 30 g cod-liver oil/kg as the sole lipid source for a further 8 weeks. At the end of the experiment the stomach clearance rate, daily food intake, body-weight gain and [14C]glucose uptake in the intestine were significantly higher in group ZDLR tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…Their Zn concentration in serum being identical, the excess lipid in diet group HFZD appears to have been responsible for the induction of Zn-deficiency-related symptoms. This is in accordance with our earlier report (Taneja & Arya, 1992). We reported that the symptoms appeared in mice when fed on a Zn-deficient diet containing cod-liver oil (30 g/kg) and maize oil (60 g/kg) as the lipid source and they disappeared, despite Zn deficiency, when the maize oil was withdrawn from the Zn-deficient diet.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Their Zn concentration in serum being identical, the excess lipid in diet group HFZD appears to have been responsible for the induction of Zn-deficiency-related symptoms. This is in accordance with our earlier report (Taneja & Arya, 1992). We reported that the symptoms appeared in mice when fed on a Zn-deficient diet containing cod-liver oil (30 g/kg) and maize oil (60 g/kg) as the lipid source and they disappeared, despite Zn deficiency, when the maize oil was withdrawn from the Zn-deficient diet.…”
Section: Discussionsupporting
confidence: 93%
“…We reported that the symptoms appeared in mice when fed on a Zn-deficient diet containing cod-liver oil (30 g/kg) and maize oil (60 g/kg) as the lipid source and they disappeared, despite Zn deficiency, when the maize oil was withdrawn from the Zn-deficient diet. The similarity of the results between the present study and the one reported previously (Taneja & Arya, 1992) clarifies that the quantity rather than quality of the fat induces the symptoms in Zndeficient mice. Associated with the reduction of body weight, significantly lower testes weights in the animals of group HFZD are in conformity with the observations of previous investigators who fed fat at 50 g/kg or above in the basal diet (Millar et al 1958;Bieri & Prival, 1966;Sandstead et al 1967;Abbasi et al 1976;Lei et al 1976;Underwood, 1977;Taneja & Nirmal, 1980;McClain et al 1984;Reeves, 1990).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations